A retrospective observational study of telehealth utilisation for mental health consultations during the COVID-19 pandemic in Australian general practice - Judith Thomas; Gorkem Sezgin; Precious McGuire; Rae-Anne Hardie; Guilherme S Franco; Margaret Williamson; Andrew Georgiou (Sax Institute, 2023)
Objectives and importance of study: Despite the abundance of mental health research during the pandemic, there is limited evidence exploring mental health presentations to Australian general practice. This study examined the utilisation of telehealth for mental health consultations in Australian general practice during the COVID-19 pandemic. The objectives were to: 1) determine the proportion of mental health services delivered via telehealth between March 2020 and November 2021; 2) determine the types of mental health consultations most frequently delivered via telehealth; and 3) model the sociodemographic characteristics of patients using telehealth mental health consultations, including consultation type. Study type: Retrospective observational study. Methods: We used Medicare Benefits Schedule service item numbers to distinguish mental health consultations in de-identified electronic general practice data. We stratified the proportions of face-to-face, video, and telephone mental health consultations by state and consultation type. We used two mixed-effects logistic models to assess the variation in the likelihood of i) a telehealth (video/telephone) compared to a face-to-face consultation and ii) a video compared to telephone consultation; by sociodemographic characteristics. Results: The study comprised 874 249 mental health consultations. Telehealth use peaked in Victoria (61.6%) during July 2020 and in NSW during August 2021 (52.5%). Telehealth use continued throughout 2021 with an increase in video consultations from July 2021 onwards in both states. Proportions of mental health treatment plan consultations via telephone decreased from July 2021 with a concomitant increase in video. Telehealth was more likely to be used by females, in Victoria, in regional/remote regions and during 2020. Video was more likely to be used than telephone for mental health treatment plans/reviews compared with mental health consultations. Compared with people aged 25-29, video was most likely to be used by ages 20-24 and least by those aged 80 and over. There was no evidence for sex differences when comparing telephone and video. Conclusions: This study presents a comprehensive understanding of the important role telehealth played in the delivery of mental health consultations during the first 21 months of the pandemic, including sociodemographics of patients utilising telehealth. The findings can assist general practices with future planning for the delivery of mental health services via telehealth.